Completely simple and regular semi hypergroups - Jafarabadi, Hossein Mousa (2012)
In this paper the notion of simple and completely simple semi hypergroups are introduced. Basic properties of these algebraic structures are considered. Some methods for constructing new kinds of these hyperstructures are presented. The regularity of semi hypergroups is considered and three structural results are proved.